Lean Manufacturing Model to improve the order fulfillment in a company in the wine sector - Diaz, Maria Isabel (2022)
The wine industry has grown in recent years causing many of the companies in the sector to improve their processes. When it comes to medium and large industrial facilities, there are always some well-known methodologies that are adopted to boost their growth and minimize logistics costs. While, in the case of PYMEs, there is no provision as such to apply any Lean Manufacturing or process management technique. The case study is Bodega Peru SAC, which presents difficulties in fulfilling the perfect order due to deficiencies in its logistics processes. The purpose of this study is based on properly managing the Supply Chain to increase its performance and reduce logistic costs. The processes that cause bottlenecks or have high error rates have been identified in the case study. Likewise, the study is based on information from researchers for the analysis of supply chain processes related to the industry.